A new device color gamut boundary description algorithm based on irregular segmentation. Issue 2 (28th April 2016) - Yin, Zhang; Yongwen, Jiang; Maohai, Lin
Abstract: The description of device color gamut is very important for color gamut mapping, which plays an important role in cross‐media color reproduction. To get a more accurate color gamut boundary, several gamut boundary description (GBD) methods have been presented in the past; however, many problems still exist in the current algorithm (e.g., accuracy and speed). In this study, we propose a new device GBD method based on irregular segmentation and evaluate it against other GBD algorithms. In the irregular segmentation method, the device color gamut is divided into the high‐chroma and the low‐chroma color parts, and the high‐chroma parts are divided into more segments through the CIELAB a*b* plane when calculating color gamut descriptors. After that, in each segment, the radii between the color points and the center point are calculated. For the color points located in the high‐chroma parts, the color point with the biggest radius is selected as the gamut boundary descriptor, and for that in the low‐chroma parts, if the corresponding outer segments are empty, the color point with the biggest radius is selected as the gamut boundary descriptor. Then, the gamut boundary descriptors are visualized in CIELAB color space using triangulation method. Finally, the irregular segmentation method is evaluated in contrast with other GBD methods using gamut mismatch index. The results show that the irregular segmentation method performs better in accuracy and has smaller variance. © 2016 Wiley Periodicals, Inc. Col Res Appl, 42, 173–181, 2017